2016
DOI: 10.3139/105.110286
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation by Transformation Plasticity under the Martensitic Transformation in Steels

Abstract: Transformation plasticity is considered as a phenomenon limiting the actual stress for any specified strain rate under conditions of phase transformation. A one-dimensional model of a steel bar strained under martensitic transformation is provided. Discussion is limited to a series of accepted assumptions, such as athermal kinetics of martensite transformation, monotonic evolution of temperature and constant transformation plasticity parameter. An equivalent tangent modulus is deduced indicating the decisive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The form of this equation is such that the martensite transformation rate decreases monotonically from the onset of the transformation at M s . 7) Due to the volume change accompanying fcc to bcc or bct crystal structures in steels, it is common practice to determine transformation temperatures, e.g. during continuous cooling, using dilatometry.…”
Section: Influence Of Microsegregation On the Onset Of The Martensitimentioning
confidence: 99%
“…The form of this equation is such that the martensite transformation rate decreases monotonically from the onset of the transformation at M s . 7) Due to the volume change accompanying fcc to bcc or bct crystal structures in steels, it is common practice to determine transformation temperatures, e.g. during continuous cooling, using dilatometry.…”
Section: Influence Of Microsegregation On the Onset Of The Martensitimentioning
confidence: 99%
“…The transformation plasticity parameter of the 700XL ferritic steel is obtained from Equation (16). The data are fitted to obtain the transformation plasticity coefficient K.…”
Section: Separation Of Transformation Plasticitymentioning
confidence: 99%
“…In contrast, Denis 12 and Zhang 13 et al argued that transformation plasticity should be considered when predicting residual stress during cooling. In studying whether transformation plasticity is taken into account for stress prediction, Xu 14 and Yao 15 et al pointed out that the presence of transformation plasticity can regulate the internal stress-strain state of the material, and Ivanov 16 et al studied transformation plasticity in martensite and found that the maximum value of stress relaxation occurs at the early stage of transformation; at the same time, significant relaxation also occurs at the late stage of 60% of the phase transformation. There is no consensus on the effect of transformation plasticity on residual stress during cooling.…”
Section: Introductionmentioning
confidence: 99%